Geo Talk Media: Microlearning-Based Innovative Learning Media To Foster Student Interest In Natural Resources Material At The South Malang Nature Laboratory. - Ihdina Rifkanisa Maharani; Alfi Sahrina; Muhammad Rafif Fadihilah; Mohammad Yusril Abidin; Ho Nhu Ngoc (JAMBURA GEO EDUCATION JOURNAL, 2024)
One of the innovative learning media that can be applied is learning video. Geo Talk Media is an innovation in education that combines the microlearning approach with multimedia technology by utilising natural resources as a laboratory in South Malang. This research aims to produce microlearning-based video learning media. The main focus of this platform is to foster student learning interest in Natural Resources material, especially those in South Malang.  The type of research used is Research and Development (RnD), using the ADDIE development model. The instrument used is an open questionnaire with qualitative descriptive data analysis and a closed questionnaire with quantitative descriptive data analysis. The research subjects were geography teachers and students of class X SMAN 1 Kepanjen. The results showed that the micro-learning approach of Geo Talk learning video media can foster student learning interest in natural resources material in the South Malang laboratory. Proven by the percentage level of 87.12% with very feasible criteria. This research is important because it can overcome the problems that are often found, namely the limited focus of students in understanding the material provided, so that the advantages of this media are effective in helping facilitate student understanding of the material taught with a microlearning approach, and can provide new experiences for students.